Desain Miniatur Pasteurisasi Susu Berbasis PLC sebagai Pengembangan Modul Pembelajaran di Laboratorium Sistem Kontrol - Rahma Nur Amalia; Ika Noer Syamsiana; Ira Zulfa (Elposys: Jurnal Sistem Kelistrikan, 2021)
The pasteurization module that has been designed and made uses a PLC type TWDLMDA20DTK as its controller with the help of expansion in the form of TM2AMM6HT. The components contained in the module include a solenoid valve, heater, RTD, SRPH1, and a cooling system. The voltage from the source is then connected to the control box and then controlled by the TWDLMDA20DTK PLC and its expansion, namely TM2AMM6HT. All components will work according to the desired system operation, namely the temperature can be stable at 63˚ C for 30 minutes with PID auto-tuning control. This process is carried out by programming a ladder diagram on the TwidoSuite application. The stabilization of the module’s operation is regulated by the auto-tuning method, where this process will automatically produce Kp, Ti, and Td values ​​contained in the Ladder diagram. This process is carried out in order to obtain a stable system operation with the expected parameters. The expected parameters include a low steady-state error value of 5-10%.